2011
DOI: 10.1177/0148558x11400583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Research and Development (R&D) Inputs and Outputs on the Relation between the Uncertainty of Future Operating Performance and R&D Expenditures

Abstract: Consistent with the uncertainty of research and development’s future benefits, prior accounting studies hypothesize and find a positive relation between research and development (R&D) and the variability of future earnings. However, prior research has assumed constant marginal productivity of R&D in the cross section. We relax this assumption and advance the accounting literature on the informational role of R&D by studying how measures of innovation outputs, namely patent counts and patent citatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(134 citation statements)
references
References 45 publications
6
120
0
8
Order By: Relevance
“…In line with this, prior studies have reported a significant positive association between patent citations, Tobin's Q, and future earnings [7,8,28,31]. A large number of citations by other firms suggests corporate sustainable growth opportunities in the field, as well as the ability of an innovation to overcome uncertainty regarding economic outcomes.…”
Section: Patent Citation and Coprporate Sustainable Growthmentioning
confidence: 56%
See 2 more Smart Citations
“…In line with this, prior studies have reported a significant positive association between patent citations, Tobin's Q, and future earnings [7,8,28,31]. A large number of citations by other firms suggests corporate sustainable growth opportunities in the field, as well as the ability of an innovation to overcome uncertainty regarding economic outcomes.…”
Section: Patent Citation and Coprporate Sustainable Growthmentioning
confidence: 56%
“…Existing studies have shown that a firm's patents with high citations are positively related to its market value [5,31] and/or future financial performance [7,8]. Based on this empirical evidence, our study examines whether this positive effect of impactful patents on firm performance is considered by financial analysts in their forecasting activities.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hunton et al (2003) observe that ROA (Return on Assets), ROS (Return on Sales) and ATO (Asset Turnover) is significantly lower for non-ERP (Enterprise Resource Planning) adopters than for ERP adopters in the third year after ERP implementation. Pandit et al (2011) measure firm performance in terms of net income and operating cash flows. They find that the mean level of future operating performance is positively associated with the quality of a firm's patents.…”
Section: Prior Research and Literature Reviewmentioning
confidence: 99%
“…Specifically, we focus on R&D activities which can be measured in terms of R&D input and output. R&D input is R&D expenditure, and R&D output is patent counts and citations (Pandit, Wasley & Zach, 2011). Using these definitions, this paper develops two hypotheses based on a network approach to multinational enterprises in an emerging economy setting and tests them on a panel data set from 317 multinational subsidiaries in China over the period [1999][2000][2001][2002][2003][2004][2005].…”
Section: Introductionmentioning
confidence: 99%